PERBANDINGAN TINGKAT KEDISIPLINAN GURU PENDIDIKAN JASMANI YANG SUDAH PNS DAN GTT DALAM PROSES BELAJAR-MENGAJAR PENJAS PADA SEKOLAH DASAR NEGERI SE-KECAMATAN RAMBIPUJI – JEMBER - ERFANSYAH, SELA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Discipline is an attitude that effort to controlling self on individual and social to develop pursuance and observance to rule and regulation based encouragement and awareness that emerge from own heart. Education is an important matter to human live, since with education human able to develop better vice versa. Government notices the important of teacher role to generation, therefore they tries to improve teacher competence by improve their prosperity through programs that they have designed, like certification program for teacher who already have PNS status. This research aim to detect the discipline rate on teacher in a matters like dressing, on time presence, on time teaching schedule, and daintiness during physical education learning process. Beside, to detect how big teacher’s discipline that already PNS and GTT on learning process at elementary school on Rambipuji District. Method that applied in this research is quantitative with comparation approach. Based research, so it can be conclude that there is no difference in the level of discipline penjaskes teachers and civil servants in terms of overall indicators GTT with a significance value of .402, but when seen by the indicator there is a difference in terms of learning activities with a significance value of .042. Keywords : discipline, physical education, PNS teacher, GTT